Use of immigration status for coercive control in domestic violence protection orders - Alsinai, Aisha; Reygers, Max; DiMascolo, Lisa; Kafka, Julie; Rowhani-Rahbar, Ali; Adhia, Avanti; Bowen, Deirdre; Shanahan, Sandra; Dalve, Kimberly; Ellyson, Alice M. (Frontiers in Sociology, 2023)
In the context of domestic violence (DV), immigration-related circumstances can be exploited by an abuser to coerce and manipulate their partner. Using an intersectional structural framework, we examine how social structures overlaid with immigration-specific experiences operate to further enhance opportunities for abuse against immigrant women. We conducted a textual analysis to identify how socially constructed systems interact with a victim-survivor's immigration status to introduce more tools for abusers to engage in coercive control and/or acts of violence in a random sample of petitioners (i.e., victim-survivors) who were granted a Domestic Violence Protection Order (DVPO) in King County, WA (n = 3,579) from 2014–2016 and 2018–2020. We hand-reviewed textual petitioner narratives and identified n = 39 cases that discussed immigration-related circumstances and related acts of violence and coercion. These narratives included threats to contact authorities to interfere with an ongoing immigration process, deportation threats, and threats that would separate families. In many cases, petitioners indicated that immigration-related threats prevented them from leaving the violent partner, seeking help, or reporting the abuse. We also found mention of barriers for victims to receive protection and gain autonomy from further abuse including a lack of familiarity with US protections and laws, and restrictions on authorizations to work. These findings demonstrate that structurally created immigration-specific circumstances provide opportunities for threats and retaliation against victim-survivors by abusers and create barriers to seeking help initially. Policy should respond to anticipate these threats in the immigrant community and engage early responders (e.g., healthcare providers, law enforcement) to support victim-survivors from immigrant communities.